Cyclic routing of unmanned aerial vehicle - Heng, Jozua Yi Jie (Nanyang Technological University, 2022)
This report proposes an alternative algorithm that uses a metaheuristic technique, Simulated Annealing, to solve for the Cyclic Routing of Unmanned Aerial Vehicles (CR-UAV) problem. This report discusses the implementation of the algorithm and provides experimental results for the algorithm. The purpose is to eventually provide an algorithm that is optimal, consistent, and reasonably scalable such that is it applicable to real world scenarios. Data are collected by running the test cases over 100 runs. The output is exported out as a Comma Separated Value (CSV) file. Analysis and processing of the output is done in Jupyter Notebook and further exported out as another CSV file. Statistics from the test results have proved that algorithm is able to solve for the CR-UAV with relative optimality and consistency under a reasonable amount of time.